2021
DOI: 10.1108/reps-03-2021-0019
|View full text |Cite
|
Sign up to set email alerts
|

Pre-COVID-19 evaluation of external debt, corruption and economic growth in South Africa

Abstract: PurposeThis study is a pre-COVID-19 exposition of the existing situation about external debt-GDP relationship, incorporating corruption into the hypothesis, making South Africa the object of the study. The aim is to examine the causal relationship between corruption, economic growth and external debt, and in the end proffer solutions to the problems arising therefrom.Design/methodology/approachThe study employed ARDL technique on time series data running from 1990 to 2019 with real gross domestic product as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…The revival of GGGD in SSA countries can be attributed to factors such as the 2008 global financial crisis shocks, adverse commodity price shocks, financial gaps in infrastructure, and a drop in official development assistance. The outbreak of COVID-19 was the most significant cause for the increase in government spending, which led to a rise in debt profiles to address financial shortfalls [ 57 , 58 ]. Studies show that out of 36 countries that have benefited from the HIPC initiative introduced by the World Bank and IMF, 33 countries are associated with SSA, which suggests debt levels are poorly managed, necessitating measures to reduce excessive debt levels.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The revival of GGGD in SSA countries can be attributed to factors such as the 2008 global financial crisis shocks, adverse commodity price shocks, financial gaps in infrastructure, and a drop in official development assistance. The outbreak of COVID-19 was the most significant cause for the increase in government spending, which led to a rise in debt profiles to address financial shortfalls [ 57 , 58 ]. Studies show that out of 36 countries that have benefited from the HIPC initiative introduced by the World Bank and IMF, 33 countries are associated with SSA, which suggests debt levels are poorly managed, necessitating measures to reduce excessive debt levels.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Olamide and Maredza [14] looked at the effect of state debt on real economic growth in South Africa from 1980 to 2014. The empirical results demonstrated that South Africa's economy is now doing badly, and this conclusion is statistically significant.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For the Republic of Congo, Melina et al (2019) determined that anti-corruption reforms could increase growth by 0.8%–1.8% per year over a 10-year period. For South Africa, Olamide and Maredza (2021) employed the autoregressive distributed lag technique to time series data running from 1990 to 2019 and concluded that corruption exerts a negative influence on economic growth, and more so in the short-run, with a 1% increase in corruption reducing growth by 0.3%.…”
Section: The Corruption and Sustainable Development Relationship In A...mentioning
confidence: 99%